2014
DOI: 10.1007/s00425-014-2216-x
|View full text |Cite
|
Sign up to set email alerts
|

Do phosphoinositides regulate membrane water permeability of tobacco protoplasts by enhancing the aquaporin pathway?

Abstract: Enhancing the membrane content of PtdInsP 2 , the already-recognized protein-regulating lipid, increased the osmotic water permeability of tobacco protoplasts, apparently by increasing the abundance of active aquaporins in their membranes. While phosphoinositides are implicated in cell volume changes and are known to regulate some ion channels, their modulation of aquaporins activity has not yet been reported for any organism. To examine this, we compared the osmotic water permeability (P f) of protoplasts iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…More particularly, the procedure for the evaluation of AQPs using Arabidopsis, tobacco and maize mesophyll protoplasts is well established (Yoo et al, 2007; Besserer et al, 2012; Ma et al, 2015). There are several methods for the delivery of macromolecules into protoplasts including, electroporation, microinjection, and PEG–calcium fusion method (Sade et al, 2009; Shen et al, 2014).…”
Section: Analytical and Functional Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…More particularly, the procedure for the evaluation of AQPs using Arabidopsis, tobacco and maize mesophyll protoplasts is well established (Yoo et al, 2007; Besserer et al, 2012; Ma et al, 2015). There are several methods for the delivery of macromolecules into protoplasts including, electroporation, microinjection, and PEG–calcium fusion method (Sade et al, 2009; Shen et al, 2014).…”
Section: Analytical and Functional Approachesmentioning
confidence: 99%
“…They further swapped transmembrane domain-3 along with the ER export diacidic motif to demonstrate its requirement in the localization. Another study conducted using tobacco protoplasts showed the role of phosphoinositides in modulating aquaporin activity (Ma et al, 2015). AQP gene ZmPIP2;4 from maize was transiently expressed in tobacco protoplasts to evaluate phosphoinositides effect on AQP expression and water flux (Ma et al, 2015).…”
Section: Analytical and Functional Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of aquaporin by PIP2 occurs only in plant cells, but has not yet been demonstrated in mammalian cells (Ma et al. ), and TRPC is included in the group of channels regulated by PIP2 (Suh & Hille, ). It is thus possible that PIP5K and its product PIP2 are involved in regulation of some ion‐transporting proteins in the apical membranes of the glandular acinar cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that increased intracellular water is the basic characteristic of cellular edema (33). AQP1 is a water channel protein and its function is mainly to transport water across the plasma membrane, contributing to water homeostasis of cells (34).…”
Section: Fsc-mentioning
confidence: 99%